Recent developments of microfluidics as a tool for biotechnology and microbiology. (February 2019) - Scheler, Ott; Postek, Witold; Garstecki, Piotr
Graphical abstract: Highlights: Microfluidics is transforming traditional techniques in biotechnology. Multi-step experiments are automated on single device in parallel reactors. Millions of parallel reactions can be conducted and analyzed in a single assay. Cells and biomolecules are precisely positioned for high-throughput analysis. Abstract : Academic microfluidics has decisively shifted in recent years from the research on phenomenology and proof-of-concept fluidic functionalities to the developments oriented at applications with biology, medicine and biotechnology in prime focus. Significant efforts are made to demonstrate that microfluidics can be used in unspecialized laboratories to perform previously mundane tasks faster and easier, or to venture into new research areas that were unavailable or unattractive when only classical means of microbiology or biotechnology were employed. Here we review a variety of biological experiments recently performed in microfluidic assays. We categorize the microfluidic systems by the key role they play in the biological experiments as: (i) controlled reaction chambers, (ii) high-throughput arrays, or (iii) micro-positioning systems. We also discuss the outlook for further development and applications of microfluidics in biological sciences.